Application Of Vortex Induced Vibration Energy Generation Technologies To The Offshore Oil And Gas Platform: The Preliminary Study - M. A. Zahari; S. S. Dol (Zenodo, 2014)
The global demand for continuous and eco-friendly renewable energy as alternative to fossils fuels is large and ever growing in nowadays. This paper will focus on capability of Vortex Induced Vibration (VIV) phenomenon in generating alternative energy for offshore platform application. In order to maximize the potential of energy generation, the effects of lock in phenomenon and different geometries of cylinder were studied in this project. VIV is the motion induced on bluff body which creates alternating lift forces perpendicular to fluid flow. Normally, VIV is unwanted in order to prevent mechanical failure of the vibrating structures. But in this project, instead of eliminating these vibrations, VIV will be exploited to transform these vibrations into a valuable resource of energy. : {"references": ["R. Fross, Concept Selection of Normally Unmanned Installations in the\nNorth Sea, Thesis (M.A), Lund University, Sweden, 2012.", "A. Beaumont, \"Field development Concept Scenarios for Pohokura,\"\nInt. J. New Zealand Petroleum Conference Proceedings, 2002.", "M. A. Azhar, U. Azimov, C. I Lim, and S.S Dol, \"Conceptual Study and\nPreliminary Design of Offshore Mariculture Farm on Decommissioned\nOil and Gas Platform,\" Proceedings of Science & Engineering\nTechnology National Conference, Kuala Lumpur, Malaysia, 2013.", "E. Goffman, \"Why Not the Sun? Advantages of and Problems with Solar\nEnergy,\" Int. J. ProQuest Discovery Guides, 2008.", "A. Vinod, A. Kashyap, A. Banerjee, and J. Kimball, \"Augmenting\nEnergy extraction From Vortex Induced Vibration Using Strips of\nRoughness/Thickness Combinations,\" Int. J. Marine Energy technology\nSymposium, 2013.", "M. M. Bernitsas, K. Raghavan, Y. Ben-Simon, and E. M. Garcia,\n\"VIVACE (Vortex Induced Vibration Aquatic Clean Energy): A New\nConcept in Generation of Clean and Renewable Energy From Fluid\nFlow,\" Int. J. Offshore Mechanics and Arctic Engineering, 2006.", "I. Ball, T. Killen, S. Sakhuja, and E. Warner, Energy Generation From\nVortex Induced Vibration, Thesis (B.S.), Worcester Polytechnic\nInstitute, United States, 2012.", "A. Hall-Stinson, C. Lehrman, and E. Tripp, Energy Generation From\nVortex Induced Vibration, Thesis (B.S.), Worcester Polytechnic\nInstitute, United States, 2011.", "R. D. Blevins, Flow Induced vibration, Thesis (Ph.D.), California\nInstitute of Technology, California, 1974.\n[10] A. Techet, Vortex Induced Vibration. MIT OpenCourseWare.\nMassachusetts Institute of Technology, United States, 2005.\n[11] C. H. Williamson, and R. Govardhan, \"Vortex-Induced Vibration,\" Int.\nJ. Fluid Mech, 2004.\n[12] Y. Omar, T. Tengku, and A. Mohamad, \"Prospects for Ocean Energy in\nMalaysia,\" Int. J. International Conference on Energy and Environment,\n2006.\n[13] R. Fitzpatrick, Oscillations and Waves. The University of Texas, United\nStates.\n[14] M. A. Zahari, Renewable Energy Harvesting using Vortex Induced\nVibration, Thesis (B.ME.), Curtin University, Malaysia.\n[15] W. He, K. Uhlen, M. Hadiya, Z. Chen, G. Shi, and E. Rio, \"Integrating\nan Offshore Wind Farm with Offshore Oil and Gas Platforms and with\nan Onshore Electrical Grid,\" Int. J. Renewable Energy, 2013."]}